2021
DOI: 10.15252/embj.2020105603
|View full text |Cite
|
Sign up to set email alerts
|

PIP2 depletion and altered endocytosis caused by expression of Alzheimer's disease‐protective variant PLCγ2 R522

Abstract: Variants identified in genome‐wide association studies have implicated immune pathways in the development of Alzheimer’s disease (AD). Here, we investigated the mechanistic basis for protection from AD associated with PLCγ2 R522, a rare coding variant of the PLCG2 gene. We studied the variant's role in macrophages and microglia of newly generated PLCG2‐R522‐expressing human induced pluripotent cell lines (hiPSC) and knockin mice, which exhibit normal endogenous PLCG2 expression. In all models, cells expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 61 publications
2
51
0
Order By: Relevance
“…Several other polymorphisms implicated as risk factors in AD, such as the R47H TREM2 mutation, result in alterations to microglial phagocytic capacity that lead to reduced clearance of Aβ aggregates and neuronal decline [18,19]. In our hiPSC derived microglia assay, PLCγ2 P522R enhanced the uptake of Aβ compared to PLCγ2 WT microglia, suggesting that the variant may positively impact directly on disease relevant pathology clearance, as previously suggested [12]. Consistent with this increased Aβ clearance, lysotracker levels, which indicate acidic vesicles such as lysosomes, were higher in both PLCγ2 HET and PLCγ2 HOM microglia variants compared to PLCγ2 WT cells.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Several other polymorphisms implicated as risk factors in AD, such as the R47H TREM2 mutation, result in alterations to microglial phagocytic capacity that lead to reduced clearance of Aβ aggregates and neuronal decline [18,19]. In our hiPSC derived microglia assay, PLCγ2 P522R enhanced the uptake of Aβ compared to PLCγ2 WT microglia, suggesting that the variant may positively impact directly on disease relevant pathology clearance, as previously suggested [12]. Consistent with this increased Aβ clearance, lysotracker levels, which indicate acidic vesicles such as lysosomes, were higher in both PLCγ2 HET and PLCγ2 HOM microglia variants compared to PLCγ2 WT cells.…”
Section: Discussionsupporting
confidence: 69%
“…PLCγ2 P522R differential selectivity is driven by cargo size. PLCγ2 P522R has previously been reported to in uence selective cargo uptake, suggesting a shift towards endocytic pathways [12]. Given the differential impact of heterozygous and homozygous PLCγ2 P522R on Aβ and synaptosome uptake, we sought to further investigate whether similar cargo selectivity differences were observed in our microglial cell model.…”
Section: Plcγ2 P522r Modulates Microglia Mediated Uptake Of Aβ and Sy...mentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, approximately 40% of the susceptibility genes identified in genetic studies of LOAD are immune- and microglia-related, suggesting that microglia are involved in modulating AD pathology [ 8 ]. To date, it is known that phospholipase C γ 2 ( PLCG2) might be important in AD due to the pervious findings that a hypermorphic variant in PLCG2 , rs72824905, is protective against AD risk [ 9 11 ]. However, the role of PLCG2 has not yet been comprehensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…PLCG2 is expected to be important in AD due to the previous findings that a hypermorphic variant in PLCG2, rs72824905, is protective against AD risk. However, the role of PLCG2 has not yet been comprehensively explored [11, 39]. A previous study has reported that reduced PLCG2 gene expression alter microglial phenotypes in 5XFAD mice, affect plaque pathology, and drive distinct transcriptional phenotypes of microglia in the presence of amyloid pathology[11].…”
Section: Discussionmentioning
confidence: 99%